The effect of red-cabbage (Brassica oleracea L. var. capitata f. rubra) ethanolic extract in cream preparation on dermis-elastic fibre thickness in male Wistar rats after ultraviolet-B rays exposure - Intan Syahirah Bt Abdul Rauap; I Wayan Sugiritama; Ni Made Linawati; I Gusti Kamasan Arijana (Intisari Sains Medis, 2018)
Background: Ultraviolet B (UV-B) rays exposure is a leading cause of sunburn, skin dryness and skin aging by influencing the dermal elastic fibers. This photoaging effect was caused by damage of fibrillin-1 as a microfibrillar network. This study aims to evaluate the effect of red-cabbage (Brassica oleracea L. var. capitata f. rubra) ethanolic extract in cream preparation on dermis-elastic fibers thickness in male Wistar rats after UV-B exposure.Methods: A randomized post-test only control group design was conducted among 25 male Wistar rats during 2 weeks. They were divided into 5 groups as follows: control group (P1), basic cream (P2), 5% ethanolic extract of red cabbage cream (P3), 10% ethanolic extract of red cabbage cream (P4), and 20% ethanolic extract of red cabbage cream (P5). The UV-B dosage used are 325 mJ/cm2 among groups prior to study. The dermis-elastic fiber thickness was assessed by Image Raster software. Statistical analysis was carried out using SPSS version 20 in measuring normality test, mean, and ANOVAResults: There was a statistically significant difference of dermal-elastic fibers thickness among groups (P < 0.05). The mean of dermis-elastic fiber thickness was 6.125±0.376 µm in P5 group, followed by 4.075±0.266 µm in P4 group, and 3.114±0.290 µm, 2.109±0.420 µm, and 1.907±0.454 µm in P3, P2, and P1 group respectively.Conclusion: Ethanolic extract of red-cabbage in a different dose of cream preparation have a statistically significant difference on the dermis-elastic fibers thickness after UV-B exposure